ISOLATION AND IDENTIFICATION OF COLIPHAGE FROM UNTREATED WASTEWATER IN KUALA PILAH NEGERI SEMBILAN - Muhammad Hafizhullah Anuar; Nur Surya Zulkifly; Nurhamimah Zainal Abidin; Sharifah Aminah Syed Mohamad; Nur Intan Hasbullah; Rashidah Iberahim (Journal of Academia)
Bacteriophages are viruses that can only infect bacterial cells and are perceptible in almost all places where living bacteria are found, as they are highly host specific. Wastewater comprises microorganisms that have become contaminated by the environment. These microorganisms, particularly bacteria, may develop antibiotic resistance and constitute a serious threat to human health. Therefore, the goal of this research is to isolate coliphage from untreated wastewater and to identify the susceptible coliform host. The method used for bacteriophage isolation is plaque formation assay and the selected plaque was further enriched and purified using the double-layer plaque technique to classify bacteriophages. Identification of susceptible coliform host using gram stain and biochemical analysis results were compared with other coliform bacteria (Klebsiella sp, Escherichia coli, and Shigella sp.) to identify the susceptible coliphage host. The isolated coliphages appear late from 2 out of 3 samples collected around Kuala Pilah town. The plaque shows were small and turbid after 7 days of incubation in 37°C. It was suspected to be a temperate phage as the plaque developed was turbid. The susceptible host shows similar biochemical characteristics as Klebsiella sp. In conclusion, the bacteriophage obtained from this study is a temperate bacteriophage from environmental wastewater that could infect a coliphage likeKlebsiella sp. Further identification of susceptible host was suggested including determination of its medical usage.